Integrating Biological Control Agents for Sustainable Management of Soybean Diseases in India - Rafi Ahmed and M M V Baig (South Eastern European Journal of Public Health, 2025)
Despite hefty production and application of new technologies for soybean production in India, the crop suffers from various diseases that induces heavy losses. This in turn place a heavy burden on the output and the quality through high-cost treatment, making it really a problem for the farmers. However, injudicious use of pesticides causes problems with secondary pest emergence, potential threat to the environment, pathogen invulnerability, and crop residues. The promise of biological control for the freeway to control major soybean diseases infecting, such as soybean rust, charcoal rot, bacterial pustule, or downy mildew. Trichoderma spp., Pseudomonas fluorescens, and Bacillus spp. are widely used as biological control agents (BCA) owing to their mechanism, which consists of antibiotics, competition, parasitism, and ISR, both suppressing pathogens and promoting plant well-being. Specific biological control strategies, such as seed treatment, soil and foliar application, as well as the compatibility of biological control with cultural practices for disease management, are discussed. The review also shows the issues involved with implementing BCA in these different agroecological regions of India. Aspects of environmental heterogeneity, lack of storage infrastructure, and farmer education are also discussed.